Structural-semantic Features and Translation Specifics of German Phraseological Units with a Colorative Component - Shchyhlo , Larysa; Antipova, Alina (Philological Treatises, 2020)
The proposed study deals with structural and semantic features, as well as translation specifics of German phraseological units with a colorative component. The relevance of the topic is determined by the fact that the presence of color notation in the composition of phraseological units with a colorative component make such units difficult to translate. At the same time, in Ukrainian translation studies there is a lack of systematic knowledge and comprehensive research on the peculiarities of the translation of German phraseological units with a colorative component. Phraseological units that use the names of colors are accompanied by evaluative connotations and correlated with a holistic picture of the world of a particular national culture. Therefore, it is not surprising that in recent years, phraseological units with a colorative component have often attracted the attention of researchers. Phraseological units accompany a person throughout his life. They give a description of the world, human activities, and the person himself. At the same time, each object of our reality is characterized by a certain color, even if it is barely noticeable and indistinct. A person perceives color not only as an objective characteristic, but also as a moral and aesthetic category. This category expresses attitude, assessment, norm. Having obtained deep symbolic semantics in the process of the development of the German language, the colors reflect the linguistic view of the world through the prism of which native speakers perceive reality. The structural and semantic difficulties of translating German phraseological units with a colorative component are due to the fact that in addition to the complex structure of such phraseological units and their figurative meaning, the difficulties of translating German phraseological units with a colorative component also include culturally specific information. Correct interpretation and translation of such phraseological units requires from the translator background knowledge, skill in mastering the techniques and means of translation.